Tinjauan Hukum Terhadap Sanksi Pidana Bagi Penolak Vaksinasi di Masa Pandemic Covid-19 - syarwan ichromi kabalmay (Fakultas Hukum Universitas Riau, 2021)
Indonesia will implement a vaccination program, but there are people who reject the program because they are afraid it will cause health problems. One state official said that vaccination was not a right, but an obligation, so if he refused, he could be punished. The formulation of the research problem is whether people who refuse vaccines can be convicted and how effective are criminal sanctions. The purpose of this research is to understand and analyze whether the imposition of criminal sanctions can be carried out, and to analyze the effectiveness of the application of criminal sanctions. The author has not found any scientific work that has anything in common with this research. This study uses a normative method. Sources of data come from primary and secondary legal materials. The analysis method is qualitative. In the discussion, vaccination is a right, but in a state of emergency turns it into an obligation accompanied by criminal sanctions. This does not intend to limit the rights and freedoms of society, but rather to guarantee recognition and respect for the rights and freedoms of every citizen. However, punishment is only applied if other legal means do not function. Criminal sanctions must be tailored to the need to protect and defend the interests of society. Criminal law is only justified if there is a need that is useful to society. Therefore, the use of criminal law that is not in accordance with the needs cannot be justified because it will be dangerous for society.